Relatório técnico do livro-reportagem olhares sobre Maria do Carmo: feminicídio, feminismo e fé - (:unkn) unknown (Universidade Federal do Pampa, 2023)
The following work is a technical report on the experimental project of a reportage book that proposes to retell a local story that is reputed to be a legend in the city of São Borja. The literary journalism book is entitled Looks About Maria do Carmo: Feminicídio, Feminismo e Fé and tells the story of Maria do Carmo Fagundes, popular saint of the municipality of São Borja, from the perspective of the narrative told by the residents and about the faith of her devotees. We write carefully and respectfully, using interview data, which allow us to recompose part of the imaginary of the city's population about the popular saint. The content produced in this book is authorial, with the participation of reports from residents who know its history, in order to draw a line between the history of Santa Popular in the municipality and the relationship of the residents' faith with it. In addition, this book proposes to bring out the misogynistic approaches that surround her story. The book initially addresses the story of Maria do Carmo, first contextualizing the historical moment and the places where the story takes place, then brings stories of residents of the city of São Borja and their relationship with the popular saint. The book was made available as an ebook, for easy access and reading. In this report, we bring a bibliographic review of the initial phase of the research, contradictory points in the narrated story and explanations about the production, writing and editing of the reportage book.
Keywords: Vítimas de homicídio – Mulheres; Folclore urbano; Lendas; Folclore urbano - Maria do Carmo - São Borja, RS; Violência contra as mulheres; Mulheres - Crimes contra; Jornalismo; Homicide Victims – Women; Urban folklore; CNPQ::CIENCIAS SOCIAIS APLICADAS